Location tracking method with visual aids scheme on TI CC2431 ZPS platform for wireless sensor network - Yongyan ZOU; Yanzhi ZHANG (Dianxin kexue)
In wireless sensor network,concerning that dramatic changes of speed in a short period of time may lead to angle effect and reduce the location accuracy for tracking,and individual scheme is difficult to improve the location tracking accuracy,a location tracking method using Kalman filter and visual aids on TI CC2431 ZPS platform was proposed.Visual aid was used on the basis of normalized cross correlation,and the position of the reference node was extracted being as landmarks according to the visual aid method,and then the KF method was used to calibrate the position estimation.The proposed method could effectively avoid the uncertainty caused by the system error in the actual dynamic environment,and reduced the angular effect of the position estimation system,and improved the location tracking accuracy.The experimental results demonstrate that more than 56 percent of the location estimates have error distances less than 2.3 meters and 1.9 meters for TI ZPS method and KF based method,more than 56 percent of the location estimates have error distances less than 1.5 meters for the proposed method.